Results From a National Mixed-Methods Study Exploring Community Health Improvement Implementation: An Opportunity to Strengthen Public Health Systems Through Collective Action. Issue 3 (21st May 2022) - Welter, Christina R.; Jarpe-Ratner, Elizabeth; Seweryn, Steven; Bonney, Tessa; Verma, Pooja; Weller Pegna, Sarah
Abstract : Context: There are multiple calls for public health agency role and workforce transformation to increase capacity to orchestrate cross-sectoral partnerships that set and implement strategies addressing the structural and social determinants of health. Mobilizing for Action through Planning and Partnerships (MAPP) may be one tool for collective action to improve population health and equity. However, little is known about the Action Cycle in MAPP and implementation of resulting community health improvement plans. Objective: To explore the characteristics of MAPP users who completed the MAPP Action Cycle and factors that facilitated or inhibited implementation activities during this phase. Methods: We used a sequential participatory mixed-methods design involving 2 phases of data collection. The first data collection phase included a Web-based survey using Qualtrics. The second data collection phase included qualitative key-informant interviews and focus groups. A national public health and health care advisory group informed the evaluation throughout the entire process to ground the process in practice and experience. Results: This study showed that some MAPP participants do not conduct implementation activities as defined by the MAPP Action Cycle and of those who do, implementation activity varies by participant experiences conducting MAPP and accreditation status. The MAPP users who completed 3 or more rounds of MAPP were more likely to align and integrate MAPP within their agencies as well as organize a collaborative implementation process with partners. More resources and skills in planning that facilitate long-range partnerships were noted as key to implementation. Conclusions: Opportunity remains to improve implementation in MAPP. National leaders should explore and build capacity and infrastructure within public health agencies and with their partners to create a system of readiness and an infrastructure that support implementation over time.